MATRIKULASI METODE DRILL DALAM MENINGKATKAN BACA TULIS AL-QUR’AN SISWA - Yuliastutik; Laila Badriyah; Siti Kholidatur Rodiyah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2024)
Learning to read and write the Koran at MTs Darul Ulum Waru Sidoarjo is an initial stage that students must take to deepen the Islamic religion. The drill method matriculation is an activity to train students' dexterity or skills which aims to increase students' knowledge and dexterity in reading and writing the Qur'an properly and correctly. This study uses a qualitative descriptive approach by revealing certain social situations by describing reality correctly, to understand phenomena that are occurring naturally. The data collection technique used by the author is using interview, observation, and documentation methods as well as the validity of the data used, namely using Persistent Observation, technical triangulation, and source triangulation. The results of the study show that the application of the Matriculation Drill Method in Improving Students' Reading and Writing of the Qur'an at Madrasah Tsanawiyah Darul Ulum Waru is by holding special lesson hours for students who will take munaqosah (exams) which are usually 2 times a week to 4 times a week to further train students in improving their reading and writing of the Qur'an. As well as innovating in using methods that make it easier for students to understand the material and perform apgreding which aims to improve students' reading and writing of the Koran and train students to be fluent in reading the Koran without halting, and reading the Koran according to with tajwid, gharib, makharijul letters.